TRADISI PENGHORMATAN MUSHAF KUNO DI DESA SAPIT, LOMBOK TIMUR - Hamzani, Yusri (Lajnah Pentashihan Mushaf Al-Qur'an, 2017)
The ancient mushaf has a duality of symbol; traditional and religious symbols. Both rules of religion and tradition oblige the people to respect the ancient mushaf. The way to respect the Mushaf in Sapit Village is various. Starting from sitting to the slaughtering a cattle before reciting and studying the mushaf. The rituals of respecting the mushaf in Sapit Village are unique. Theory of social evolution is interesting to use in analyzing that reality. It is for the reason of variety of Sapit Village people and its dynamics, Sapit village then has changed the way of respecting the mushaf. Before 1967, people of Sapit Village were embracing Islamic sect known as wetu teluwhich is an acculturation between religion and tradition. Moreover, during that period, the people thought the ancient mushaf to have contained a magical power and could save them from disaster. However, their perception changed when Tuan Guru Zainuddin Mamben came to Sapit Village and taught them theology. The people do not respect the mushaf anymore the way they did before the Tuan Gurucame. Their tradition has transformed into tradition known as Tokol (sitting when seeing the mushaf ). Today, people have forgotten sacredness of the ancient mushaf. The development of mushaf printing industry makes people equal among ancient mushaf and other printed mushaf.KeywordsWetu Telu Islamic Sect, respecting the ancient mushaf, transformation.